ENSURING GENDER EQUALITY AND EMPOWERING WOMEN AND GIRLS IN PLACES OF IMPRISONMENT - Abduganieva G. K. (Journals Park Publishing, 2025)
This article describes the need to ensure gender equality and empower women and girls in prisons. Inclusive and adaptive education, which involves the inclusion of convicted women and girls in the processes of professionalization and building their own vector of professional development as future full-fledged university graduates in the space of professional qualifications.
Keywords: Employment, education, gender equality, inclusive education.